Management of BUMDes in an Effort to Increase the Status of Villages to “Independent” in Banten Province - Giyanto, Bambang; Murtinah, Tintin Sri; Pangaribuan, Delvi Adri Rahmadana (KnE Social Sciences, 2025)
This study aims to determine the management of BUMDes (Village-Owned Enterprises) in Disadvantaged Villages, Advanced Villages, and Joint Business Entities (BUMDes Bersama) in Bayah District and Cilograng District, Lebak Regency, Banten, in order to alleviate poverty in Disadvantaged Villages and raise their status to Independent Villages. The management indicators used in this study are from Luther Gullick’s theory, namely planning, organizing, staffing, directing, coordinating, reporting, and budgeting. This research uses qualitative methodology with a descriptive approach. Data were obtained by interview, observation, and document review. The results indicate that the establishment of BUMDes is not based on identifying needs, but on the demands of the law. In organizing, some businesses have not been carried out properly, and their staff is only limited to local village staff, so that it is very limited in choosing professional personnel. The direction has not been carried out optimally from stake holders related to BUMDes or BUMDes Bersama and coordination has not been carried out optimally so that business development is still limited to the village level. However, reports have been carried out properly, namely through internal monitoring mechanisms and village deliberations; and budgeting for BUMDes or BUMDes Bersama is still limited to capital participation from the local village government, and involves the community or other parties to invest in BUMDes or BUMDes Together. Improvements are needed in planning the establishment of BUMDes and in planning the business field. In the utilization of staff, it is necessary to find professional staff and to pay attention to their welfare. Regarding directions, the ministry and institutions must be involved in fostering BUMDes and Joint BUMDes and to include the community and other parties to invest in BUMDes or Joint BUMDes.